Task-Based Language Teaching To Enhance Speaking Skills In Boarding School Students A Classroom Action Research - Ika Wulaningsih; Nur Hidayanto Pancoro Setyo Putro; Sukarno; Dwiyani Pratiwi; Tri Setiani; I Made Rian Irwanto; Intan Widora (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The aim of this study is to investigate how Task-Based Language Teaching (TBLT) enhances the speaking skills of junior high school students in an Islamic boarding school context and how it enhances the quality of the teaching and learning process. Due to the dominance of teacher-centred instruction and limited student engagement in such contexts, this study proposes to apply a more interactive and student-centred approach. This study employed the Classroom Action Research (CAR) design, involving 29 male students in grade 7 over two cycles. Each cycle consists of four phases: plan, action, observation, and reflection. Data were collected through interviews, classroom observations, reflective teaching journal, and oral proficiency tests to earn both qualitative and quantitative data. The findings revealed significant enhancements in students’ speaking performance. The students’ mastery level increased from 31.03% (initial data) to 65.52% (cycle 1) and 93.10% (cycle 2). Students demonstrated enhanced fluency, vocabulary, and confidence, along with enhanced motivation and participation in communicative tasks. TBLT also helped reduce speaking anxiety and encouraged more meaningful language use inside and outside the classroom. Despite some challenges, such as limited access to technology and the need for additional scaffolding for certain students, this study demonstrated that TBLT is a viable approach to enhancing speaking skills in a boarding school context. The findings also suggest that TBLT helped to foster students’ communicative competence and enrich English language instruction in similar educational contexts. Recommendations are offered for sustaining TBLT implementation and for future research on long-term impacts and differentiated scaffolding.